Material samples & mock up and test report and technical specification of sealer and putty and emulsion with the reply of BRACU Project Manager (RFA-442_Rev B) (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of PDF version of drawings.